A low risk of nosocomial transmission of subclinical tuberculosis to neonates in a postpartum care center under COVID-19 control measures - In Kyoung Kim; So Jung Kim; Kyoung Hee Bae; Mi Young Kim; Ji Eun Oh; Mi Gyeong Lee; Young Ae Kang; Jin Su Song (Osong Public Health and Research Perspectives, 2022)
We report the results of investigating and managing a tuberculosis (TB) exposure in a postpartum care center. Among the contacts exposed to a nursing assistant with subclinical TB, 5 of 44 neonates (11.4%) had positive tuberculin skin tests (TSTs) at 3 months of age, and all the TST-positive neonates received the Bacille Calmette-Guérin vaccination. Seven of 28 healthcare workers (25.0%) and 1 of 3 household contacts (33.3%) were positive in the initial or repeated interferon-gamma release assay. None of the contacts developed TB disease during the study period. Annual TB examinations of healthcare personnel at a postpartum care center under the Tuberculosis Prevention Act in South Korea enabled the early detection of subclinical TB, which reduced the risk of transmission to neonates under strict coronavirus disease 2019 prevention measures.